Energy system contribution to 400-metre and 800-metre track running - Duffield, R.; Dawson, B.; Goodman, C. (Journal of Sports Sciences, 2005)
As a wide range of values has been reported for the relative energetics of 400-m and 800-m track running events, this study aimed to quantify the respective aerobic and anaerobic energy contributions to these events during track running. Sixteen trained 400-m (11 males, 5 females) and 11 trained 800-m (9 males, 2 females) athletes participated in this study. The participants performed (on separate days) a laboratory graded exercsie test and multiple race time-trials. The relative energy system contribution was calculated by multiple methods based upon measures of race &Vdoti;O2, accumulated oxygen deficit (AOD), blood lactate and estimated phosphocreatine degradation (lactate/PCr). The aerobic/anaerobic energy system contribution (AOD method) to the 400-m event was calculated as 41/59% (male) and 45/55% (female). For the 800-m event, an increased aerobic involvement was noted with a 60/40% (male) and 70/30% (female) respective contribution. Significant (P ?<?0.05) negative correlations were noted between race performance and anaerobic energy system involvement (lactate/PCr) for the male 800-m and female 400-m events (r=???- 0.77 and -0.87 respectively). These track running data compare well with previous estimates of the relative energy system contributions to the 400-m and 800-m events. Additionally, the relative importance and speed of interaction of the respective metabolic pathways has implications to training for these events.